Impact of the Russia-Ukraine war on African agriculture, trade, poverty, and food systems - Laborde Debucquet, David; Matchaya, Greenwell C.; Traoré, Fousseini (2023)
On February 24, 2022, Russian troops entered Ukraine, sparking one of the most intense conflicts in recent years. As of September 2023, the conflict is still active and continues to raise concerns. Russia, Ukraine, and Belarus (which has been indirectly involved in the conflict) are key actors in world markets for two product groups critical for African countries: food (mainly cereals and vegetable oils) and fertilizers. With world markets already severely disrupted by the COVID-19 pandemic, the new crisis in the Black Sea region, combined with climate shocks around the world, has further disrupted supply chains and increased prices. Since African countries are net food and fertilizer importers, the situation continues to raise serious concerns. This chapter offers an in-depth analysis of the conflict’s impact on Africa’s agricultural and food systems, with particular attention to the food and fertilizer sectors, the two main channels through which the shock has been transmitted. It is important to understand the extent of Africa’s exposure and vulnerability to the conflict’s impacts, including the impact on the ground in Africa in terms of lost or delayed agricultural production and increased food security risks. Moreover, this is an opportunity for policymakers not only to develop solutions that will mitigate the impact of the present crisis at the national, regional, and continental levels, but also to learn from the experience for future crises. As countries respond, it is also important to respect and improve the trade rules at the global level to avoid measures that may exacerbate the effects of the crisis.